Cholestatic Hepatic Injury Induced by Carbimazole: A Case Report and a Thorough Literature Review - Bassem Al Hariri (19180066) (2025)
Carbimazole, a thionamide derivative, is widely used for hyperthyroidism but carries a rare risk of hepatotoxicity, including cholestatic injury. A 42‐year‐old man developed severe cholestatic jaundice 4 weeks after carbimazole initiation. Laboratory findings showed marked hyperbilirubinemia (peak: 650 μmol/L) with elevated ALP (366 U/L). Viral, autoimmune, and biliary causes were excluded. Liver biopsy confirmed cholestasis. Carbimazole was discontinued, corticosteroids initiated, and radioiodine therapy planned. Bilirubin levels gradually improved over 8 weeks. Carbimazole‐induced cholestasis, though rare, necessitates prompt recognition and alternative hyperthyroidism management. Routine liver monitoring is crucial. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.70498